Restructuring of the aluminium industry : implications for developing countries. - Lines, Thomas (1990)
Reviews changes in an apparently solidly entrenched market structure over the last decade. Concludes that despite the rapid world-wide deconcentation of ownership of the industry in recent years, in general all Third World nations engged in this sector face the continuing strength of aluminium multinational corporations. This situation of dependency need not last forever, and the biggest priority for developing countries in the industry must be to develop their own technological capabilities.